2022
DOI: 10.1186/s12870-022-03937-7
|View full text |Cite
|
Sign up to set email alerts
|

Root system architecture of historical spring wheat cultivars is associated with alleles and transcripts of major functional genes

Abstract: We evaluated root system architecture (RSA) of a set of 58 historical spring wheat cultivars from Pakistan representing 105 years of selection breeding. The evaluations were carried out under control and water-limited conditions using a high-throughput phenotyping system coupled with RhizoVision Explorer software. The cultivars were classified into three groups based on release year as cultivars released pre-1965, released between 1965 and 2000, and cultivars released post-2000. Under water-limited conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…(Beyer et al 2019). In the past, only 58 Pakistan's historical wheat cultivars were evaluated for root architecture system (Maqbool et al 2022a). Therefore, the present study screened the larger Pakistan's landraces and historical wheat cultivars (n = 161) to provide better insight into the prevalence of genetic variations related to RSA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Beyer et al 2019). In the past, only 58 Pakistan's historical wheat cultivars were evaluated for root architecture system (Maqbool et al 2022a). Therefore, the present study screened the larger Pakistan's landraces and historical wheat cultivars (n = 161) to provide better insight into the prevalence of genetic variations related to RSA.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly large variations for root traits were observed for large exotic wheat germplasms like n = 323 (Li et al 2019), n = 196 (Xu et al 2021), and n = 201 cultivars representing 200 years of breeding and selection history (Beyer et al 2019). In the past, only 58 Pakistan's historical wheat cultivars were evaluated for root architecture system (Maqbool et al 2022a). Therefore, the present study screened the larger Pakistan's landraces and historical wheat cultivars (n = 161) to provide better insight into the prevalence of genetic variations related to RSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimizing RSA traits is important not only for abiotic stress tolerance but also for efficient nutrient and water acquisition ( Gupta et al., 2017 ; Griffiths et al., 2022 ). RSA traits primarily include root length, surface area, and the number of root tips, which influence the major components and spatial arrangement of root systems, significantly affecting water and nutrient uptake ( Atkinson et al., 2015 ; Maccaferri et al., 2016 ; Liu et al., 2019 ; Li et al., 2020 ; Ma et al., 2022 ; Maqbool et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous breeding programs predominantly focused on aboveground traits such as disease resistance, grain quality, and harvest index, while the application of RSA traits has been limited due to the complexity of phenotypic evaluation ( Rogers and Benfey, 2015 ; Roselló et al., 2019 ; Mehrabi et al., 2020 ; Rufo et al., 2020 ; Salarpour et al., 2020 ; Ober et al., 2021 ; Pariyar et al., 2021 ; Saini et al., 2021 ). Previous studies have indicated that the RSA traits are influenced by environmental factors and controlled by minor genes ( Xie et al., 2017 ; Soriano and Alvaro, 2019 ; Maqbool et al., 2022 ). To accelerate the progress of breeding for RSA-related traits, it is imperative to identify the significant associated genomic regions ( Soriano and Alvaro, 2019 ; Yang et al., 2021a ).…”
Section: Introductionmentioning
confidence: 99%